Consumer response to brand renaming as part of an international standardisation strategy. (1st January 2013) - Ringeisen, Petra; Hünerberg, Reinhard
This article deals with the problem of changing names of fast moving consumer products as it is often inevitable when pursuing international brand standardisation. The authors focus on the crucial question of how customers cope with such brand name changes and present a new model of consumer reactions. In order to gain a better understanding of the underlying psychological processes when consumers are confronted with name changes, annoyance about the name change is introduced as an intervening variable, with perceived fit between original and new brand name and attachment to the brand as determinants. An empirical investigation in two fast moving consumer good categories in Germany, using structural equation modelling, largely supports the hypotheses. On the basis of the empirical findings, practical implications and future research directions are presented.